Beyond PHA: Stimulating intracellular accumulation of added-value compounds in mixed microbial cultures. (October 2021) - Pinto-Ibieta, F.; Serrano, A.; Cea, M.; Ciudad, G.; Fermoso, F.G.
Highlights: Dissolved oxygen has a greater impact on the type and amount of produced compound. PHA production is favored at dissolve oxygen concentrations lower than 3 mg/L. Dissolved oxygen concentrations above 3 mg/L favor the synthesize of PG and TAG. OLR and cycle length were identified to have an impact on the accumulation of PHA. Abstract: This review compiled and analyzed the operational conditions (dissolved oxygen, feast and famine ratio, sequential batch reactor cycle length, organic loading rate (OLR), pH, C/N, and temperature) established during the feast and famine culture strategy for the mixed microbial cultures (MMC) selection to understand how these variables could affect the synthesis of polyhydroxyalkanoates, polyglucose, triacylglycerides, levulinic acid and adipic acid from non-fermented substrates. According to the reported information, the dissolved oxygen has a greater impact on the type and amount of produced compound. In a lesser extent, the OLR and the cycle length were identified to have an impact on the accumulation of polyhydroxyalkanoates, whose accumulation was favored at lower OLR and longer cycle lengths. Thereby, the information of this work will allow the design of future strategies for the simultaneous accumulation of compounds of interest other than the polyhydroxyalkanoates or understand the operational conditions that would optimize the polyhydroxyalkanoates production.